Edukasi Penerapan Teknologi Fermentasi melalui Pembuatan Kefir dan Yogurt - Khairunnisa, Amalia; Pratika Viogenta; Nani Kartinah; Arnida Arnida; Sutomo Sutomo; Fadlilaturrahmah Fadlilaturrahmah (Jurnal Nusantara Berbakti, 2024)
Fermentation technology can increase added value to agricultural, food and other products. Through fermentation, raw materials can be converted into products with higher selling value, such as cheese, yogurt, tempeh, wine, beer, and so on. Many fermented products are beneficial for health, for example kefir and yogurt which contain good probiotics. for digestion. Kefir is a type of fermented milk whose manufacture uses various microorganisms to produce lactic acid products with by-products such as ethanol, free fatty acids and acetaldehyde. Kefir is made by adding yeast which contains many microorganisms from the lactic acid bacteria and yeast groups, while yogurt is fermented milk with lactic acid bacteria (LAB).  This service activity aims to increase people' knowledge and skills regarding the application of fermentation technology, starting from the meaning of fermentation, fermentation methods to high-value products produced from the fermentation process. In this activity, socialization activities were carried out regarding the development of fermentation technology, especially kefir and cow's milk yogurt, as well as practices on how to make it among the residents of Balitra Jaya Permai Loktabat Utara. The results show an increase in residents' knowledge and skills regarding fermentation through pretest and posttest activities as well as practical activities.